APEMAN, BABAD DALAN, AND RASULAN CEREMONIES: THE WAYS TO RESPECT KI AGENG GIRING IN SODO VILLAGE, GUNUNGKIDUL, YOGYAKARTA - Dahlia Kusumaningrum (Conscientia, 2020)
This article is about the history of Apeman, Babad Dalan, and Rasulan ceremonies and the procession of Apeman, Babad Dalan, and Rasulan ceremonies, the kinds of the ceremonies offerings and the meaning. The purpose of this article is to elaborate the history of the ceremonies, the procession of the ceremonies, the kinds of the offerings and the meaning. In the data collection, I collected the primary data from field research. Field research is done by doing informal interviews, direct observations, and participation in the ceremonies. Secondary data was from library research and internet. The writers used books, magazine, journals and websites to complete the data. From this study, the writers found out that Ki Ageng Giring has many values for Sodo villagers. One of them is that they have passion to maintain and preserve Apeman, Babad Dalan, and Rasulan ceremonies to honor and respect Ki Ageng Giring as the ancestor of Sodo village.